UPAYA KETAHANAN RUMAH TANGGA KELUARGA MATRIFOKAL: STUDI TERHADAP KELUARGA TENAGA KERJA WANITA PERSPEKTIF TEORI FENOMENOLOGI - Hidayati, ST Nor (Indonesian Journal of Shariah and Justice, 2025)
The aim of this research is to explain the resilience efforts of TKW families in Sidomulyo Village, Jakenan District, Pati Regency when studied using Alfred Schutz's phenomenological theory. This study used qualitative research methods. Researchers use this type of field research. Data collection techniques in this research were by means of interviews, observation and documentation. This research directly targets the research object, namely matrifocal families, village officials, community leaders in Sidomulyo Village, Jakenan District, Pati Regency. The data analysis method in this research uses the Miles and Huberman analysis model, data analysis methods include: data reduction, data display and conclusion. The results of this research show that the phenomenon of wives working as migrant workers to meet the family's economic needs occurs in Sidomulyo Village, Jakenan District, Pati Regency. The factor that motivates them to migrate abroad is economic factors. Low economic conditions are the main driver. Efforts to maintain the resilience of matrifocal family households in Sidomulyo village by maintaining good communication between husband and wife, apart from maintaining communication, commitment to always be faithful, are also important efforts in matrifocal families.